The Influence of Accountability and Performance-Based Budgeting on Financial Performance at the Fire and Rescue Department of Medan City - Ririn Dwindina Anggia; Rifdah Riyan Dara; Mutia Riska Faridani; Sovia Lolita Apriani Pardede; Hasrul Siregar (Jurnal Ilmiah Accusi, 2026)
This study aims to examine the influence of accountability and performance-based budgeting on the financial performance of the Fire and Rescue Department of Medan City. A quantitative explanatory research design was employed to investigate the causal relationships among the research variables. Primary data were collected through questionnaires distributed to 63 Civil Servants selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS software. The results indicate that accountability has a positive and significant effect on financial performance. Performance-based budgeting also has a positive and significant effect on financial performance. Furthermore, accountability and performance-based budgeting simultaneously have a positive and significant influence on financial performance, with the regression model explaining 59.2% of the variation in financial performance, while the remaining variation is attributable to other factors beyond the scope of this study. These findings suggest that strengthening accountability and implementing performance-based budgeting are essential for improving the financial performance of public sector organizations, particularly institutions responsible for fire and rescue services